Effects and Mechanisms of Acupuncture on Diarrhea-Predominant Irritable Bowel Syndrome: A Systematic Review - Zhang, Gezhi; Zhang, Tao; Cao, Zeng; Tao, Zijing; Wan, Tianhao; Yao, Mengxi; Su, Xiaolan; Wei, Wei (Frontiers in Neuroscience, 2022)
Background Irritable bowel syndrome (IBS) is a common disorder of gut-brain interaction with challenging treatment. According to evidence-based studies, acupuncture is likely to be a promising therapy and subservient adjunct for IBS. Mechanism study of acupuncture based on related clinical trials of high quality, nevertheless, is still vacant. Aim This study aims to assess the results and qualities of current clinical evidence and conclude the relevant pathophysiological mechanisms and therapeutic effects of acupuncture on IBS with diarrhea (IBS-D). Methods Literature from four databases, namely, PubMed, Cochrane Library, EMBASE, and Web of Science, was systematically searched to obtain eligible randomized controlled trials (RCTs), which contained mechanism research of acupuncture treatment in IBS-D patients. Two independent reviewers completed data extraction and quality evaluation using the RevMan 5.4.1 software. Results Ten trials that covered 19 items related to mechanism research were included in this review. Acupuncture was reported to improve IBS-D symptoms and quality of life, with positive effects in regulating brain-gut peptides, cerebral activities, neuroendocrine functions, psychological state, and inflammatory GI and hypersensitive intestinal tracts. Conclusion Acupuncture has potential influence on pathophysiology alterations such as regulating brain-gut peptides, altering cerebral connectivity and activity, promoting neuroendocrine functions and mental state, and mitigating inflammation as well as hypersensitivity of bowels in IBS-D patients, but further studies of high quality are still necessary. Systematic Review Registration [https://www.crd.york.ac.uk/PROSPERO], identifier [CRD42022320331].